A Convenient Synthesis of new Phenanthrolinone and Naphthyridinone Derivatives: Evaluation of their Biological activity (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
A novel and effective synthesis of substituted acetamide via smiles rearrangement is described. Treatment of phenols with 2-chloroacetamide in the presence of sodium hydroxide and DMA where substituted phenols, which contain electron withdrawing groups, are more reactive for smiles rearrangement. The reaction followed by cyclization of the product by E.A.A. afforded the corresponding substituted phenanthrolinone and naphthyridinone in good yields and showed higher activity against (G- and G+, Eschierchia coli and Staphylococcus aureus respectively) and good activity toward Aspergillius flavus and Candida albicans.